Avoiding migration at open mesh plug inguinal hernioplasty. Issue 5 (May 2022) - Brown, Charlotte; O'Hare, Rachael; Stephenson, Brian M.
Abstract: The open repair of groin hernias is often augmented with prosthetic biomaterials (mesh) as this favours a lower recurrence rate. The use of such prostheses may be associated with various complications including migration the frequency of which is unclear. A 29-year review of this complication after mesh plug hernioplasty is undertaken and technical advice described to avoid this. Highlights: Open Mesh plug inguinal hernia repair needs to be performed methodically. Abstract : Open mesh plug inguinal hernioplasty, Plug migration, Mesh complications.